A new genus for Oxyomus morosus Harold, 1869 (Eupariini) and redefinition of Oxyomus setosopunctatus A. Schmidt, 1911 (Aphodiini) (Coleoptera Scarabaeidae: Aphodiinae) - Dellacasa, Marco; Stebnicka, Zdzislawa (Instituto de Ecología, A.C., 2001)
The lectotypes of Oxyomus morosus Harold, 1869 from Chile and Oxyomus setosopunctatus A. Schmidt, 1911 from Mexico are herein designated. The systematic position of O. setosopunctatus within Aphodiini is ascertained, and Oxyomus morosus is transferred to the new genus Oxyataenius (Eupariini).